STUDI KELAYAKAN BISNIS USAHA JASA DESAIN GRAFIS DAN DIGITAL PRINTING PADA GEDE PROJECT DESIGN - Ni Ketut Murdani; Ni Putu Andini Desiyanti Laksmi (Universitas Mahendradatta Denpasar, 2021)
In the current era of globalization, as time goes by, technology will become more sophisticated, the role of graphic design in all business fields is needed. This can be proven by the number of business fields that utilize the expertise of graphic designers. The need for promotional design which is now increasingly prevalent in the business world, making graphic design is required to be able to develop itself in making a product that can attract public interest.This research was conducted with the aim of knowing the feasibility of the Gede Project Design Industry in terms of market aspects, technical aspects, and management and human resources aspects using qualitative descriptive methods, while financial financial aspects were analyzed using quantitative descriptive methods with manual systems through the help of the Microsoft Excel program.The analysis results obtained from market aspects, technical aspects, as well as aspects of management and human resources, the Gede Project Design industry is still categorized as still feasible to run, but there are several things that need to be evaluated and improved in marketing strategies related to promotional activities that still rely on the door to door strategy. word of mouth so that the absorbed market share is still not according to the desired target, then the problem with company management does not have a permanent workforce. Meanwhile, the analysis of the financial aspects shows that the Gede Project Design industry is feasible to run. This can be seen from the NPV (Net Present Value) obtained 0 and a positive value of IDR 28,164,030. The resulting IRR (Internal Rate Of Return) value the commercial bank interest rate of 12.88%. The resulting payback period from the investment age of 2.5 years. The Profability Index (PI) obtained is 1 which is 1.78.